2016
DOI: 10.1038/srep39748
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and carbon-water coupling jointly control the interannual variability of global land gross primary production

Abstract: Carbon uptake by terrestrial ecosystems is increasing along with the rising of atmospheric CO2 concentration. Embedded in this trend, recent studies suggested that the interannual variability (IAV) of global carbon fluxes may be dominated by semi-arid ecosystems, but the underlying mechanisms of this high variability in these specific regions are not well known. Here we derive an ensemble of gross primary production (GPP) estimates using the average of three data-driven models and eleven process-based models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 56 publications
7
40
1
Order By: Relevance
“…The variations in GPP in both the El Niño types were closely associated with variations in soil moisture, namely water availability largely dominated by precipitation (Figs. 4b, d and 5b, d), and this result was consistent with previous studies (Zeng et al, 2005;Zhang et al, 2016). Warm temperatures during El Niño episodes can enhance the ecosystem respiration, but dry conditions can reduce it.…”
Section: Regional Contributions Characteristics and Their Mechanismssupporting
confidence: 92%
“…The variations in GPP in both the El Niño types were closely associated with variations in soil moisture, namely water availability largely dominated by precipitation (Figs. 4b, d and 5b, d), and this result was consistent with previous studies (Zeng et al, 2005;Zhang et al, 2016). Warm temperatures during El Niño episodes can enhance the ecosystem respiration, but dry conditions can reduce it.…”
Section: Regional Contributions Characteristics and Their Mechanismssupporting
confidence: 92%
“…Satellite and eddy-covariance measurements have shown positive greening or productivity responses to increases in light availability in tropical wet forests (Huete et al 2006, Saleska et al 2007. In contrast, water-limited sites have shown reduced photosynthesis during the dry season, thus different tropical forest types can exhibit asynchronous responses to climatic variability with water more limiting in dry sites and light more limiting in wet forests (Pau et al 2010, Zhang, Xiao, et al 2016. The dry season greening of tropical forests, even in wet sites, has been intensely debated (Samanta et al 2010, Morton et al 2014) and there are rarely ground measurements of tropical leaf phenology to corroborate satellite measures (Asner & Alencar 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Because SIF is more intimately coupled with photosynthetic biophysical processes, benchmarking with SIF is expected to provide additional information on vegetation activity. Indeed, Zhang et al (2016c) used SIF data to obtain an ensemble GPP by weighting estimates by multiple models. We confirmed that monthly GPP simulated by the biome models shows comparable seasonal change with that in SIF ( figure S3).…”
Section: Benchmarkingmentioning
confidence: 99%